Fracture behaviour of a fibre reinforced earthen material under static and impact flexural loading. (15th April 2016) - Aymerich, F.; Fenu, L.; Francesconi, L.; Meloni, P.
Highlights: We studied the effect of hemp fibres on the mechanical performance of an earthen material. The samples were subjected to static and impact bending. Hemp fibres greatly increase the fracture resistance and the energy absorption capacity. Both unreinforced and reinforced materials show a strong sensitivity to the rate of loading. The post-cracking performance is improved by increasing the fibre fraction and length. Abstract: The study investigates the enhancements in the load carrying capacity, crack resistance and energy absorption properties provided by the addition of hemp fibres in an earthen material. Notched earthen samples reinforced with two fibre contents (2% and 3% in weight) and three fibre lengths (10, 20, and 30 mm) were manufactured and tested under static and impact bending to investigate and compare the influence of the reinforcement on the fracture resistance of the soil material at low and high strain rates. The results of the experimental analyses show that the incorporation of fibres greatly improves the peak load, the post-crack strength, the ductility and the energy dissipation of soil under both static and impact bending. The mechanical response of both unreinforced and reinforced samples is significantly affected by the rate of loading, with samples exhibiting higher values of strength and absorbed energy under impact than under static bending. For both static and impact loading, the post-crack response of the material at large deformations is clearly improved by increasing the fibre content and, at the same fibre content, by increasing the fibre length.